The Representation of Islam Under Modern Turkey in Orhan Pamuk’s Snow - ALFIAN EKA PURNAMA (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2017)
Abstract Representation is a part of literary study that subjectively viewed the cultural context and powerin a society. This is kind of language used by people to say and represent the world meaningfully. In2002, Nobel Prize author “Orhan Pamuk” published his first political-historical novel entitled Snow, thenovel creates a public debate during its publication. The issue of Islam against Secularist appeared inthis novel, which presents the struggle of Headscarf girl and Islam Fundamentalist in Kars City. Thisstudy aims on three different parts to portray the representation of Islam, they are: Representation ofIslam under the Media, Headscarf culture and how Ka as a main character views the tension betweenModern and Traditional city. By focusing on the topic that related to Islam and its problem with SecularState in the novel, this study captured the representation of Islam in different aspect such asrepresentation of Islam under the media, secularist and political Islam. Similarly, headscarf as a part ofreligious dresscode and secular media portray in this study which is achieved by application of Culturaland Representation theory from Stuart Hall and discussed three elements of representation such as:Reflective, Intentional and constructionist. Referring to the findings, the study concludes that therepresentation of Islam under Modern Turkey presents the depiction of Islamic figure, headscarf girl andthe main character perspective about traditional vs modernism. Keywords: Representation, Headscarf, Islam, Secular, Turkey. Abstrak Representasi adalah bagian dari studi sastra yang secara subjektif memandang konteks budayadan kekuasaan dalam suatu masyarakat. Ini adalah jenis bahasa yang digunakan oleh orangorang untukberbicara dan mewakili seluruh dunia dengan penuh makna. Pada tahun 2002, penulis yang menerimaHadiah Nobel